The effect of ultraviolet on direct current potentials of the human skin - A. O. Lazarev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Aim of the study. investigation of the suntan on the level of omnipresent electrical potential of skin in frames of development of the hypothesis about the melanocyte participation in skin electrical activity formation. Material and methods. 11 men and 11 women on summer holyday took part in investigation. The relationship between the levels of skin omnipresent electrical potential and the reflection factor were investigated. The omnipresent electrical potentials were registered as the potential differences between the two areas on skin using the Orion 261S pH meter and the liquid Ag/AgCl electrodes of the same company. The reflecting factor was estimated with the help of the spectroradiometer LI-1800 ("LI-COR") using the included intgrational sphere 1800-12 coated with barium sulfate. Hole size was 1,45 cm. The reflection factor was estimated at the wave band 375-800 nanometers with the scanning pitch 1 nm. Main results. There is a mathematical relation between the magnitudes of potential differences and the reflection factors of the areas of sunburnt skin and the areas of the skin not affected with sun at wave light 620-729 nm. The relationship could be approximated in linear equation. Spearman correlation factor between these two parameters was -0,43 (p = 0,045), between the differences in levels of skin omnipresent electrical potential and the reflection factors of the sunburnt skin was r = -0,52 (p = 0,01), between the differences of the electrical potentials of sunburnt skin and the skin not affected with sun was r = -0,28 (p = 0,2). The presented results of investigation and the data from literature allow to conclude that there is a positive correlation between the level of omnipresent electrical potential of skin and the quantity of melanosomes filled with melanin. Conclusion. It is suggested that melanocytes take part in formation of the skin electrical activity via melanosomes filled with melanin. At the same time the melanocyte contribution in skin electrical activity is not assessed.